The path to green economy: Do environmental taxes and renewable energy transition matter in OECD countries? - Sodiq Arogundade; Adewale Samuel Hassan (World Development Sustainability)
This study examines the effect of environment tax and renewable energy transition on the green economic growth of 37 OECD countries from 1990 to 2021. The empirical results show that environmental tax has a non-linear impact on green economic growth. The nonlinearity is characterised by a U-shape relationship, indicating that at the initial stage, environmental taxes negatively impact green growth. The impact then becomes positive and significant at a later stage when environment tax reaches a threshold of 3.53 % for production-based green growth and 2.46 % for demand-based green growth. By replacing fossil fuels in electricity generation, heating, transportation, and industrial processes, the study finds that transitions to renewable energy improve air pollution and the green economy. The estimated results are reassuringly robust to alternative measures of green economic growth (production-based and demand-based Co2 productivity) and various estimators such as instrumental regression, fixed effect instrumental regression, Machado and Silva quantile regression and JKS Granger non-causality results. The study recommends that since environmental taxes do not improve green economic growth immediately, it is important to gradually implement these taxes to allow industries and consumers time to adjust and invest in green alternatives.